Developement Of A Light Attenuator Based On Glassy Reflections - Ferria, K.; Belkhir, N. (University of Eloued جامعة الوادي, 2012)
The light intensity control of a luminous source is a very important operation in many optical applications. Several types of light attenuator exploiting different optical phenomena like diffraction, absorption, and reflection exist and they differ principally in the maximum attenuation rate, the control range, the sensitivity and the spectral band. In the presented work, we have developed and designed a light attenuator based on the progressive decrease of the transmitted light intensity, when it undergoes multiple vitreous reflections across eight plates glasses arranged in a roof shape. Several tests were carried out using a laser light as a source. We have shown that the attenuation rate can be controlled by the choice of the incidence angle on the glasses slides, in addition we have confirmed, for the case of perpendicular polarization of the laser light, that the attenuation obeys to a linear function. The obtained results are very close to those predicted theoretically.
Articale in Journal of fundamental and Applied Sciences Vol. 04 N. 01
Keywords: light attenuator, Fresnel equation, light polarization.